The Perceptions of Families of Comatose Patients in the Intensive Care Unit: A Qualitative Study - Mansoureh Karimollahi; Zahra Tazakori; Roghiyeh Falahtabar; Mehdi Ajri-Khameslou (Iran University of Medical Sciences, 2021)
Background: There are specific challenges regarding the perceptions of families of comatose patients in Intensive Care Units (ICUs). Identifying these perceptions may attract the cooperation of families with nurses and provide better care for patients. This study aimed to explore the perceptions of families of comatose patients in ICUs. Methods: This was a qualitative content-analysis study. Seventeen families with comatose patients were recruited by the purposive sampling technique. The necessary data were generated by semi-structured interviews, continued until data saturation, and concurrently analyzed by an inductive content analysis method. Results: Four main categories were manifested, including shock and disbelief, the effort for adaptation, exhaustion, and burnout, as well as hope and support. Conclusion: The obtained results signified the importance of nurses' awareness concerning the family members' perceptions of their comatose patient status in ICUs. The relevant findings reflected the need for nurses to pay attention to the feelings and emotions of the families of these patients.